Selective Recovery of Dissolved Metals from Mine Drainage Using Electrochemical Reactions - Park, Sang-Min; Shin, Su-Yeon; Yang, Jung-Seok; Ji, Sang-Woo; Baek, Kitae (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Heavy metal contamination caused by abandoned mines is a serious environmental problem in Korea. Acid mine drainage (AMD) contains various toxic heavy metals as well as dissolved iron and aluminum that contaminate downstream areas. Recent research on the removal and recovery of metals in AMD has attempted to solve environmental problems related to AMD. In a previous study, we reported that dissolved Fe, Al, Cu, and Zn/Ni can be recovered from AMD via selective precipitation. However, the recovery process consumed too many chemicals, both neutralizing and oxidizing agents. To solve this problem, the current intensity study investigated the potential of electrochemical methods to produce oxidizing and neutralizing agents that will decrease the need for chemicals. Fe(II) in anolyte was directly oxidized to Fe(III) on the electrode surface, not by oxidants. Anode material and current intensity influence oxidation reaction rate. Graphite anode resulted in the highest oxidation rate, and higher current intensity enhanced oxidation rate. In the connecting media experiments, the cation exchange membrane (CEM) and anion exchange membrane (AEM) demonstrated high loss of Fe (about 40 similar to 50%) caused by precipitation on the membrane surface and in the catholyte. The Fe loss used for salt bridge (SB) was about 10%. The catholyte contained a high concentration of hydroxide generated by the cathodic reaction that can be used as a neutralizing agent. The neutralizing agent produced by electrochemical reactions can be used to selectively recover dissolved metals. Additionally, the use of solar cell reduced energy consumption. Based on the results, it is possible to oxidize Fe(II) to Fe(III) while producing neutralizing agents for selective recovery of dissolved metals from AMD. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: REVERSE-OSMOSIS CONCENTRATE; WASTE-WATER TREATMENT; FERROUS IRON; PRECIPITATION; ELECTRODES; OXIDATION; ZN; CU; FERROZINE; HYDROXIDE